PERANCANGAN SISTEM BERBASIS WEB UNTUK MANAJEMEN PEMINJAMAN ASSET PADA PT MITRA SERVICES INFOTAMA - Angga Esa Maulana; Aziz Wirangga; Dwi Purnama Sari; Maulana Ardhiansyah; Fajar Agung Nugroho (Journal of Research and Publication Innovation, 2026)
The asset lending process at PT Mitra Services Infotama is still carried out manually using paper forms and recording in Microsoft Excel. This method causes various problems, such as data input errors, verification delays, difficulties in monitoring real-time item availability, and inefficient report recapitulation processes. This study aims to design and implement a web-based asset lending system using a prototype method. Data was obtained through observation, interviews with HRGA and employees, and literature studies to strengthen the theoretical foundation. The system development stage includes needs analysis, process flow design, database design, interface creation, core function development, and user evaluation. The results show that the developed system is capable of handling the loan process, approval, returns, item data management, and reporting automatically. The system is also able to display item availability in real-time, thereby minimizing errors and increasing HRGA productivity. The system implementation has been proven to improve the efficiency and orderliness of asset administration at PT Mitra Services Infotama.